Development of victimology in Serbia - Nikolić-Ristanović Vesna (Temida)
This paper intends to review and analyze development of victimology in Serbia. Development of victimology in Serbia is presented chronologically, through three periods: the period from 1980 to 1992, period during the wars on the territory of the former Yugoslavia (1992-2000) and period after political changes 2000. At the end, development in Serbia is assessed in the context of development of victimology as an academic discipline and achieved level of protection of the rights of victims in Serbia.